(untitled) (Bangladesh Critical Care Journal, 2024)
Background: The liver is a vital organ that serves a number of purposes in our body. It may be harmed by pollutants, substances with toxic effects, and long-term, unchecked drug use. Green tea is a well-liked beverage that has gained popularity recently and may have hepatoprotective properties. Objective: To observe the effect of green tea (Camellia sinensis) on paracetamol induced liver damage in Long Evans male rats. Methods: From July 1st, 2018, to June 30th, 2019, this study was conducted in the Department of Physiology at Sir Salimullah Medical College (SSMC), Dhaka. For the purpose of the study, thirty (30) male Long Evans rats, weighing between 150 and 200 grams and 90 to 120 days old, appeared to be in good health. They were split into two groups after 14 days of acclimatization: Group A, which served as the control group, and Group B, which served as the experimental group (green tea pretreatment and paracetamol treated). Group A1 (baseline control group) and group A2 (paracetamol treated control group) comprised the subdivided control group. There were ten rats in each of these groups. For 28 days, the rats were all fed a baseline diet. The baseline control group was given normal saline (20 ml/kg/day) orally every day for 28 days in addition to their basal diet. For the final three days of the study—the 26th and 28th—the paracetamol-treated control group was given oral paracetamol at a dose of 1.5 g/kg/day. During the final three days of the study period (the 26th and 28th days), the experimental group was given oral paracetamol (1.5g/kg/day) and an ethanolic extract of green tea (500 mg/kg/day) for a total of 28 days. On day 29, every rat was sacrificed. Following the sacrifice, liver samples were taken. Hepatic contents of malondialdehyde (MDA) were measured by using standard laboratory method. Histopathology of liver was also done by using standard laboratory procedure in the department of pathology, SSMC. Version 22 of the Statistical Package of Social Science (SPSS) for Windows was used to do the statistical analysis. The data were displayed as mean±SD. To compare the results, one-way ANOVA, post hoc Bonferroni, and Chi-square tests were used, where appropriate. A p value of less than 0.05 was regarded as significant. Result: When compared to the baseline control group, the mean malondialdehyde concentration in the liver was significantly (p) greater in the green tea pretreatment, paracetamol treated, and control groups who received paracetamol treatment. Once more, the groups treated with green tea and paracetamol had mean malondialdehyde concentrations in their livers that were significantly (p) lower than those of the paracetamol group. Additionally, 0% of the rats in the baseline control group, 100% of the rats in the paracetamol-treated group, and 30% of the rats in the green tea-pretreated and paracetamol-treated group had abnormal histological findings of the liver. Conclusion: This study revealed that green tea has hepatoprotective effect against paracetamol induced liver damage in Long Evans male rats. Bangladesh Crit Care J September 2024; 12 (2): 145-152